2014
DOI: 10.1039/c4ta02434f
|View full text |Cite
|
Sign up to set email alerts
|

Doped h-BN monolayer as efficient noble metal-free catalysts for CO oxidation: the role of dopant and water in activity and catalytic de-poisoning

Abstract: Using first principles approach, we investigate the catalytic activity of noble metal-free n-doped (C→B, O→N) hexagonal boron nitride (h-BN) monolayer for CO oxidation. To be mentioned CO adsorption ability, and hence the preferred Eiley-Rideal (ER) and Langmuir Hinshelwood (LH) mechanism for CO oxidation is dopant-dependent: CO is chemisorbed on O-doped h-BN (OBN) while it interacts physically with C-doped h-BN (CBN) surface. Even though both C and O doping create similar donor states below the Fermi level (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…active sites. 13 29,53 In order to give a good measure of the intrinsic ability of h-BNNS/Cu(111) to catalyze CO oxidation, the Sabatier activity was also deduced following the previous theoretical studies. 6, the CO molecule is initially adsorbed near O* (IS2) with C-O* distance of 2.63 Å and the distance between h-BNNS and the first metal layer is about 2.51 Å.…”
Section: Activity Of Co Oxidation On H-bnns/cu(111)mentioning
confidence: 99%
“…active sites. 13 29,53 In order to give a good measure of the intrinsic ability of h-BNNS/Cu(111) to catalyze CO oxidation, the Sabatier activity was also deduced following the previous theoretical studies. 6, the CO molecule is initially adsorbed near O* (IS2) with C-O* distance of 2.63 Å and the distance between h-BNNS and the first metal layer is about 2.51 Å.…”
Section: Activity Of Co Oxidation On H-bnns/cu(111)mentioning
confidence: 99%
“…On pure h-BN surface the energy required to dissociate the H 2 molecule into two H atoms is more than 2.29 eV, suggesting that dissociation at ordinary temperatures is quite unlikely. 41 In order to calculate the dissociation barrier, we performed Black dotted line is for guide to the eye to show nearest active sites. 57 However, in our case the doped COBN system is itself acting as a catalyst.…”
Section: Bond Exchange Mechanismmentioning
confidence: 99%
“…77 It is noticeable that the higher the Sabatier activity, the more favorable the mechanism. It is found that the Sabatier activity for the TER mechanism is 1.16 eV at room temperature, which is higher than those for the LH (1.00 eV) and ER (À0.39 eV) mechanisms.…”
Section: Co Oxidation Over Ag 1 -V B /Bnmentioning
confidence: 99%